THE CONTRIBUTION OF MAHMUDHODJA BEHBUDI TO THE FORMATION AND DEVELOPMENT OF EDUCATION SYSTEM OF TURKESTAN - Begbudieva, Parvina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article highlights and describes the characteristic features of the pedagogical views, fundamental scientific ideas of M. Behbudi on the issues of ensuring prosperity and sustainable development of Turkestan through the reform of the education system. It also analyzes the emergence and spread of the Jadid movement in Turkestan in the late 19th - early 20th. The rich heritage of each country contains the roots of spirituality, morality and culture. The generation inherits their independence, its citizens decided to create a state and society in such a way that they are oriented towards the revival of spiritual values. They are passed on from generation to generation. After gaining independence, the people of Uzbekistan decided to build their state and society in their own way, paying special attention to the revival of spiritual values.